DESIGNING E-BUKHARY SHOP APPLICATION USING THE BUSINESS TO-BUSINESS (B2B) MODEL BASED ON A WEBSITE - RM, Rusman; As’ad, Ihwana; Alwi, Erick Irawadi (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2023)
Ongoing technological developments have brought progress in the form of online sales applications. This online sales technology is often also referred to as E-Commerce. Services at the Sinar Bukhari Store for resellers who want to buy goods are still manual and simple, the sales process still uses the WhatsApp group, making it difficult for resellers and also for the shop if there are purchases of goods simultaneously. Resellers also have trouble ordering if the admin they contact is inactive, if new items are sent via the WhatsApp group, the old items will be buried in the group, making it difficult for resellers to order items that have been stockpiled. Then the solution to the problem where the E-Bukhary shop application will be made with a website-based business to business (B2B) model uses the application of prototyping techniques which make plans quickly and gradually so that potential users tend to be quickly assessed. In the E-bukhary shop application, there is a shop feature that involves admins and resellers to simplify the sales process according to the items available. through trials using black box testing in terms of interface scale 1-5 the value is 88% with very good assessment criteria, in terms of application performance a score of 88.8% is included, including very good criteria. in terms of the application database, a score of 86.6% was generated which included very good assessment criteria, then on the missing or damaged application function aspect, a value of 90% was produced in very good criteria, the last on the termination aspect resulted in a value of 86.2% or in very good criteria